The European venture capital landscape: An EIF perspective. Volume VI: The impact of VC on the exit and innovation outcomes of EIF-backed start-ups - Elitsa Pavlova; Simone Signore (European Investment Fund, 2021)
We use competing risks methods to investigate the causal link between venture capital (VC) investments supported by the EIF and the exit prospects and patenting activity of young and innovative firms. Using a novel dataset covering European start-ups receiving VC financing in the years 2007 to 2014, we generate a counterfactual group of non-VC-backed young and innovative firms via a combination of exact and propensity score matching. To offset the limited set of observables allowed by our data, we introduce novel measures based on machine learning, network theory, and satellite imagery analysis to estimate treatment propensity. Our estimates indicate that start-ups receiving EIF VC experienced a significant threefold increase in their likelihood to exit via M&A. We find a similarly large effect in the case of IPO, albeit only weakly significant. Moreover, we find that EIF VC contributed to a 13 percentage points higher incidence in patenting activity during the five years following the investment date. Overall, our work provides meaningful evidence towards the positive effects of EIF's VC activity on the exit prospects and innovative capacity of young and innovative businesses in Europe.
Keywords: G24; G34; M13; O32; O38; 330; EIF; venture capital; public intervention; exit strategy; innovation; start-ups; machine learning; geospatial analysis; network theory